Competitive performance of elite olympic distance triathletes: Reliability and smallest worthwhile enhancement - Paton, C. D.; Hopkins, W. G. (Sportscience, 2005)
PURPOSE: The reliability of competitive performance of athletes in a given sport provides an estimate of the smallest worthwhile change in performance, which is crucial when testing athletes and when assessing factors that affect performance in that sport. We have therefore analyzed the reliability of athletes competing in international Olympic-distance triathlons. METHODS: We obtained official results from websites for triathlons performed before drafting in the cycling stage was permitted. We analyzed times for 103 athletes who entered two or more of nine such races over 19 months. Our measure of reliability was the typical race-to-race variation of an athlete's time, derived as a coefficient of variation by analysis of log-transformed times. RESULTS.: (a) Typical race-to-race variations were: swim 1.6%, cycle 2.3%, and run 3.6%. When combined independently or dependently with the durations of each phase (20, 60 and 35 min), these variations yielded predicted variations in total time of 1.6% or 2.6% respectively, whereas the observed variation was 1.8%. (b) Transition times, which were available for three races, averaged 89 s for the swim-cycle and cycle-run transitions combined. Between-athlete variation in these times in each race was 5.2, 5.6 and 7.8 s, or ~0.1% of the mean total time of 115 min. (c) Analysis of reliability between all possible pairs of races showed no substantial effect of time between pairs (14-567 days). (d) Reliability between pairs of races held in normal environmental temperatures was better than when at least one of the pair was held in hot conditions (typical variations of 1.6% and 2.0% respectively). (e) The top 10% of triathletes, who averaged 3.4% faster than the average triathlete, had substantially smaller variations than the other triathletes for total time (1.1%) and for each of the three stages (swim, 1.2%; cycle, 1.3%; run, 2.5%). In triathlons where drafting in the cycle stage is permitted, variation in total time of the top triathletes is probably determined by the run alone and is therefore ~0.8%. CONCLUSIONS: (a) Factors that affect performance of individual elite triathletes act largely independently in the three phases. (b) No worthwhile gains in performance are possible in the transitions. (c) Elite triathletes' performance is remarkably stable over a 19-month period. (d) The outcome of a triathlon staged in a hot environment is somewhat less predictable than normal. (e) The smallest important change in race time for a top triathlete (half the variation in total time) is ~0.5%, which in current triathlons has to be achieved via changes of at least 1.2% in running speed.